2019
DOI: 10.1016/j.ijrobp.2019.06.2352
|View full text |Cite
|
Sign up to set email alerts
|

Single-Fraction Stereotactic Radiosurgery vs. Hippocampal-Avoidance Whole-Brain Radiotherapy for Patients with 10-30 Brain Metastases: A Dosimetric Analysis

Abstract: Top 10 highest ranked radiomic features were combined, one at a time, with the clinical features, resulting in a very significant (p<0.001) increase in AUC from the addition of the top 9 radiomic features, and no increase from adding the 10 th best radiomic feature. An optimized combination of radiomic and clinical features resulted in a dramatically higher performance (resampled AUC: meanZ0.792, 95% C.I of meanZ0.790-0.793) compared to clinical features alone (0.676, 0.674-0.678). Conclusion: The increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The step‐wise increase in feasibility of SRS alone for increasing number of intracranial lesions has been well documented, initially starting with one to three metastases, eventually increasing to ≤10 16–18 . Case reports and retrospective series have also described the feasibility of SRS for patients with greater than ten metastases 19,20 . SRS in the future will be primarily constrained not by the number of lesions requiring treatment, but rather by the volume of metastatic disease and by the length of time the patient can be on the table undergoing treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The step‐wise increase in feasibility of SRS alone for increasing number of intracranial lesions has been well documented, initially starting with one to three metastases, eventually increasing to ≤10 16–18 . Case reports and retrospective series have also described the feasibility of SRS for patients with greater than ten metastases 19,20 . SRS in the future will be primarily constrained not by the number of lesions requiring treatment, but rather by the volume of metastatic disease and by the length of time the patient can be on the table undergoing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Case reports and retrospective series have also described the feasibility of SRS for patients with greater than ten metastases. 19,20 SRS in the future will be primarily constrained not by the number of lesions requiring treatment, but rather by the volume of metastatic disease and by the length of time the patient can be on the table undergoing treatment. A SIT plan will be able to minimize that time while still minimizing dose to normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Constraints on acceptable hippocampal dosing were obtained from the protocols of NRG CC001 and CC003 and a previous study by Gondi et al [25][26][27] Constraints were converted to a single-fraction scheme using equivalent doses in 2 Gy fractions with an a/b of 2. 20,21,23,28 Hippocampal constraints for single-fraction GK-SRS were D 100 4.21 Gy, D 40 4.50 Gy, and D max 6.65 Gy. Successful hippocampal-sparing was defined as meeting all constraints in both the unilateral and bilateral hippocampi.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Multiple SRS modalities have previously been shown to be capable of achieving hippocampal dose levels lower than those seen in HA-WBRT in the treatment of extensive brain metastases, often without the need for purposeful hippocampal-avoidance. [20][21][22][23] Additionally, in a comparison of 4 SRS modalities, Zhang et al showed that frame-based technologies such as Gamma Knife (GK-SRS) lead to more dramatic dose fall off and lower hippocampal dosing when treating 3 to 10 brain metastases. 20 Such evidence suggests that GK-SRS is a favorable option for patients with lesions located in close proximity to the hippocampi, the most commonly cited risk factor for excessive hippocampal dosing in SRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation